(untitled) (Revista del Instituto de Investigación Musicológica "Carlos Vega", 2025)
Critical music editing, as a musicological theory, is recent in Latin America. Among its merits, we find the recovery of materials for musicians and researchers. However, the emergence of technology has changed the way we work. This article discusses the incidence of technology and digital humanities on notated music. It starts with the peripheral gaze of the permanent crisis that characterizes academic production in Latin America. It is supported by the main critical edition theorists, and it is complemented by the contribution from Latin American musicology. Texts analyzing the modes of production problems in editing and publishing in the digital age have been essential. At the methodological level, the research is bibliographical and documentary and includes systematization of digital sources. Among the conclusions, it is highlighted that critical music editing in the region, its archives, publishing centers, and distribution are undergoing transformation, but with little international reach. Therefore, this document on the perspectives and scope of the score as a product today hopes to generate reflections in line with the complexities of culture in the information age.